Management of African economic trees for new research, the review of Entandrophragma genus (Meliaceae) - (:unkn) unknown (My University, 2019)
Entandrophragma genus includes exclusively African species (10 to 12), five of which are on the IUCN Red List. Characterized by a taxonomic evolution that has resulted in an important synonymy of species names (36-3 7) and insufficient ecological knowledge, it is the richest in valuable species exploited as timber in Africa. This important exploitation is likely to compromise their durability in the absence of sustainable management. Our study is mainly based on scientific data (e.g., publications), economic data (production and export statistics) and legal data (laws and regulations); on management plans and inventory reports. The heavy industrial exploitation as artisanal does not always proceed in the respect of a validated management plan, nor of the duration of the rotations which would make it possible to reach a rate of reconstitution likely to perpetuate the resource which these species represent. Their sustainable management requires the development and respect of management measures to make their exploitation sustainable in the long term. This exploitation must be based on an adequate management of natural stands and on reforestation as well as on conservation measures. The research to be developed must focus on their growth rate (eg, in the face of climate change), the analysis of stable rings and isotopes, the evaluation of their stocks (production, biomass, carbon), their spatial distribution and molecular phylogeny, the improvement of their natural regeneration, their reproduction, phenology and anatomy, as well as the reinforcement of other relevant lines of research to guarantee the durability of these forest species.
Keywords: African Research